Synthesis and Characterization of Visible-Light Active Nitrogen-Doped TiO2 Photocatalyst - Cahyorini, K.; Suwardi; Narsito; Indriana, K. (Asian Journal of Chemistry, 2011)
Nitrogen-doped titania (N-doped TiO2) has been synthesized through the hydrolysis of Nsubstituted titanium isopropoxide precursors followed by annealing treatment in air at desired temperatures. The resulting N-doped TiO2 were characterized using TGA, XRD, BET, XPS, TEM and UV-VIS spectrophotometer. The XRD result showed that the structure of N-doped TiO2 was anatase. The crystallite size of N-doped TiO2 increased with the increase of N/Ti proportion. The pore properties were investigated from nitrogen gas sorption analyzer, showing a mesoporous structure of its N-doped TiO2 with a high specific surface area and a sharp pore radius distribution. The substitution of oxygen sites with nitrogen atoms in the TiO2 structure was confirmed by X-ray photoemission spectroscopy (XPS). The doping of nitrogen could extend the absorption edge into the visible-light region leaded to a clear decrease in the band gap on N-doped TiO2 (compared to pure titania and Degussa P25). The adsorption capacity and adsorption equilibrium constant were also improved by the doping of nitrogen. Catalytic application on methylene blue photodegradation under visible-light irradiation indicated that N-doped TiO2 provide better activity comparing to the pure ones.